China’s Military Engagement in The Pacific Region: Implications For Australia’s Defence and National Security Policy - Muhammad Ferdy Aditya; Khoirul Amin; Devy Indah Paramitha (Papua Journal of Diplomacy and International Relations, 2024)
The Pacific region has become a major focus of international attention following indications of increasing Chinese military involvement in the past decade. This involvement has raised significant concerns, especially for countries in the region, including Australia. As one of the regional powers and traditional actors in the Pacific, Australia faces complex national defense and security policy challenges as a result of Chinese military involvement in the region. Using a qualitative approach with desk study analysis, this paper attempts to explain the implications of Chinese military involvement in the Pacific region for Australia's national defense and security policy through the framework of security dilemma analysis and strategic perspectives in foreign policy making. This paper finds that China's military presence in the Pacific region affects defense strategy and poses new security challenges for Australia, including increasing security pressures and changes in Australia's defense strategy. In response, Australia has taken proactive steps by strengthening cooperation with regional allies, enhancing defense capabilities and strengthening security diplomacy in the Pacific region as a form of transformation of its defense policy. KEYWORDS: China’s military engagement; Australia; Pacific Region; defence strategy; national security policy